Parents’ and Teachers’ Views on Academic Performance among Multilingual Young Learners - Muh. Hasan Basri (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This research focuses on young learners with multi-language ability, Indonesian & English, in its implementation at both school and home. This study examined how young students can speak Indonesian and English fluently as well as how it affects their academic performance at school. The main sources of information in this study were parents and teachers. Data were collected from 1 tuition center and 1 elementary school in Manado. The data included questionnaire, interview notes from both parents and teachers, along with researcher’s observation notes. Academic performance of students is measured based on semester report from schools and quarterly report from tutoring consisting of 3 subjects, English, Science, and math. Those subjects selected are considered as preeminent subject by teachers and parents. The research results factors supporting young learners be able to speak more than one language and how multilingualism affects the academic performance of young learners at school on those 3 selected subjects.